1998
DOI: 10.1021/bi980910h
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Site for Soluble Cytochromes on the Tetraheme Cytochrome Subunit Bound to the Bacterial Photosynthetic Reaction Center Mapped by Site-Directed Mutagenesis

Abstract: The crystallographic structure of the Blastochloris (formerly called Rhodopseudomonas) viridis tetraheme cytochrome subunit bound to the photosynthetic reaction center (RC) suggests that all four hemes are located close enough to the surface of the protein to accept electrons from soluble cytochrome c2. To identify experimentally the site of this reaction we prepared site-directed mutants of Rubrivivax gelatinosus RCs with surface charge substitutions in the bound cytochrome subunit and studied the kinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
50
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 59 publications
9
50
0
Order By: Relevance
“…Recently, we showed direct evidence through mutagenesis on the cytochrome subunit of Rubrivivax gelatinosus that electron transfer to the cytochrome subunit from soluble cytochromes occurred via electrostatic interactions between negatively charged amino acids surrounding heme-1 and positively charged amino acids on the soluble cytochromes (12), which is consistent with a suggestion by Knaff et al (13). These charged residues on the cytochrome subunit are well conserved among many purple bacteria so far examined, suggesting that the most distant heme-1 works as a direct electron acceptor from the soluble electron carriers (9).…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Recently, we showed direct evidence through mutagenesis on the cytochrome subunit of Rubrivivax gelatinosus that electron transfer to the cytochrome subunit from soluble cytochromes occurred via electrostatic interactions between negatively charged amino acids surrounding heme-1 and positively charged amino acids on the soluble cytochromes (12), which is consistent with a suggestion by Knaff et al (13). These charged residues on the cytochrome subunit are well conserved among many purple bacteria so far examined, suggesting that the most distant heme-1 works as a direct electron acceptor from the soluble electron carriers (9).…”
supporting
confidence: 91%
“…It has been shown that electron transfer reactions from soluble electron donors to the cytochrome subunit are controlled by charge interactions (12,13). The study of site-directed mutagenesis in R. gelatinosus has shown that negatively charged amino acids (Glu) surrounding the heme-1 (positions 82, 113, and 129 in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quinone oxidation taking place at the cyt bc 1 membrane protein complex establishes a proton gradient across the membrane, which is converted to chemical energy at the ATP synthase complex. The electrons are returned back to the RC by the periplasmic soluble electron carrier cyt c 2 that is supposed to bind to the C chain of the RC, probably close to the outermost heme group to reduce the oxidized hemes (4).…”
mentioning
confidence: 99%